The Validity of Signing an Authentic Deed by a Notary Virtually in the Covid-19 Pandemic - Deslyn, Cheryl; Sitorus, Rolib (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
The purpose of this writing is to find out the legal consequences carried out by Notaries who are signing the deeds virtually in the Covid-19 pandemic situation and to find out the urgency of changes that occur regarding authentic deeds that virtually will obtain certainty, benefit and legal protection not only for notaries but also for the community. The results of the research and analysis in this writing are that electronic signatures have actually been regulated in Indonesia in Law Number 19 of 2016 concerning Information and Electronic Transactions. It's just that virtual signing of deeds using electronics has not yet obtained a strong legal basis in Indonesia. Legal certainty also cannot be achieved because there are still conflicting provisions in Law Number 2 of 2014 concerning the Office of a Notary. During the Covid-19 pandemic, many professions were able to carry out their duties by utilizing electronics but notaries were excluded because there were no specific rules that clearly regulated it and there were various legal consequences which resulted in uncertainty, injustice and no legal protection for notaries. Therefore, changes to laws and regulations or legal products are needed in order to achieve legal synchronization and harmonization. The government needs to increase the role of the notary in accordance with the times and regulate the legal force and data authenticity as well as the power of electronic deeds in proof which have been an obstacle so far.